Effect of ultrasonic treatment on the yield of humic acids from Karakeche coal deposit (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This work investigates the effect of ultrasound on the yield of humic acids from Karakeche coal and their physicochemical properties. Karakeche coal, oxidized under natural conditions, is suitable for humic acid extraction, with a humic acid content of 60% in oxidized coal. In addition to oxidized coals, Karakeche deposit also contains unweathered coals with humic acid content ranging from 6-15%, considered off-spec due to being coal fines. The aim of this study is to increase humic acid yield by modifying coal structure. Ultrasound treatment is one method to intensify humic acid extraction from coals, potentially increasing their yield.
Keywords: humic acids, oxidized coal, alkaline extraction, ultrasonic extraction, physicochemical properties